2018
DOI: 10.31768/2312-8852.2018.40(4):282-287
|View full text |Cite
|
Sign up to set email alerts
|

OXIDATIVE AND MUTAGENIC EFFECTS OF LOW INTENSITY GSM 1800 MHz MICROWAVE RADIATION

Abstract: Aim: Despite a significant number of epidemiological studies on potential carcinogenicity of microwave radiation (MWR) from wireless devices and a bulk of experimental studies on oxidative and mutagenic effects of low intensity MWR, the discussion on potential carcinogenicity of low intensity MWR is going on. This study aims to assess oxidative and mutagenic effects of low intensity MWR from a typical commercial model of a modern smartphone. Materials and Methods: The model of developing quail embryos has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…ESR is designed to determine the interactions between unpaired electrons and the environment. ESR was used to measure the rates of superoxide and nitrogen oxide generation caused by microwave radiation [ 23 ].…”
Section: Methods For the Assessment Of Microwave Radiation Injuriesmentioning
confidence: 99%
See 4 more Smart Citations
“…ESR is designed to determine the interactions between unpaired electrons and the environment. ESR was used to measure the rates of superoxide and nitrogen oxide generation caused by microwave radiation [ 23 ].…”
Section: Methods For the Assessment Of Microwave Radiation Injuriesmentioning
confidence: 99%
“…Oxidative stress, one of the most important mechanisms of microwave radiation-induced biological injuries, has been considered a result of the imbalance between pro-oxidant and antioxidant systems [ 19 ]. The common indicators implemented to examine oxidative stress included 1) free radicals (such as reactive oxygen species [ROS], nitric oxide [NO], and superoxide) [ 23 , 40 , 41 , 156 , 211 , 226 , 227 , 245 ], 2) antioxidant indicators (enzymes such as superoxide dismutase [SOD], catalase [CAT], glutathione peroxidase [GSH-px], and non-enzymes [such as glutathione [ 246 ], TAC, TAS, and TOS]) [ 17 , 19 , 97 , 191 , 209 , 247 ], and 3) oxidation products (such as MDA, conjugated dienes, protein carbonyl [PCO] and 8-hydroxydeoxyguanosine [8-OHdG]) [ 17 , 45 , 97 , 191 , 247 ]. A few reports indicated that free radicals might have adverse effects on cells and increase the oxidation of DNA bases, lipids, and proteins after microwave exposure [ 17 , 45 , 97 , 191 ].…”
Section: Indicators Of Microwave Radiation-induced Biological Injuriementioning
confidence: 99%
See 3 more Smart Citations